An osteopontin‐derived peptide inhibits human hair growth at least in part by decreasing fibroblast growth factor‐7 production in outer root sheath keratinocytes. (1st June 2020) - Alam, M.; Bertolini, M.; Gherardini, J.; Keren, A.; Ponce, L.; Chéret, J.; Alenfall, J.; Dunér, P.; Nilsson, A.H.; Gilhar, A.; Paus, R.
Summary: Background: Given that unwanted hair growth (hirsutism, hypertrichosis) can cause major psychological distress, new pharmacological treatment strategies with safe and effective hair growth inhibitors that do not destroy the hair follicle (HF) and its stem cells need to be developed. Objectives: To establish if osteopontin‐derived fragments may modulate human hair growth given that human HFs express the multifunctional, immunomodulatory glycoprotein, osteopontin. Methods: Our hypothesis was tested ex vivo and in vivo by using a newly generated, toxicologically well‐characterized, modified osteopontin‐derived peptide (FOL‐005), which binds to the HF. Results: In organ‐cultured human HFs and scalp skin, and in human scalp skin xenotransplants onto SCID mice, FOL‐005 treatment (60 nmol L −1 to 3 μmol L −1 ) significantly promoted premature catagen development without reducing the number of keratin 15‐positive HF stem cells or showing signs of drug toxicity. Genome‐wide DNA microarray, quantitative reverse‐transcriptase polymerase chain reaction and immunohistochemistry revealed decreased expression of the hair growth promoter, fibroblast growth factor‐7 (FGF7) by FOL‐005, while cotreatment of HFs with recombinant FGF7 partially abrogated FOL‐005‐induced catagen promotion. Conclusions: With caveats in mind, our study identifies this osteopontin‐derived peptide as an effective, novel inhibitory principle for human hair growth ex vivo and in vivo, which deserves systematic clinical testing in hirsutism and hypertrichosis. What's already known about this topic? The treatment of unwanted hair growth (hypertrichosis, hirsutism) lacks pharmacological intervention, with only few and often unsatisfactory treatments available. Osteopontin is prominently expressed in human HFs and has been reported to be elevated during catagen in the murine hair cycle. What does this study add? We tested the effects on hair growth of a novel, osteopontin‐derived fragment (FOL‐005) ex vivo and in vivo . In human hair follicles, high‐dose FOL‐005 significantly reduces hair growth both ex vivo and in vivo . What is the translational message? High‐dose FOL‐005 may provide a new therapeutic opportunity as a treatment for unwanted hair growth.